2012
DOI: 10.2147/opth.s28112
|View full text |Cite
|
Sign up to set email alerts
|

Current options for the treatment of optic neuritis

Abstract: Optic neuritis can be defined as typical (associated with multiple sclerosis, improving independent of steroid treatment), or atypical (not associated with multiple sclerosis, steroid-dependent improvement). Causes of atypical optic neuritis include connective tissue diseases (eg, lupus), vasculitis, sarcoidosis, or neuromyelitis optica. In this manuscript, updated treatment options for both typical and atypical optic neuritis are reviewed. Conventional treatments, such as corticosteroids, therapeutic plasma e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 119 publications
(122 reference statements)
0
11
0
2
Order By: Relevance
“…Optic neuritis has been analyzed prospectively by the Optic Neuritis Treatment Trial, which has previously reported a relationship between optic neuritis and multiple sclerosis. [1][2][3][4] The Optic Neuritis Treatment Trial looked at the clinical findings, natural history, and treatment aspects, but unfortunately only included adults with optic neuritis.…”
Section: Introductionmentioning
confidence: 99%
“…Optic neuritis has been analyzed prospectively by the Optic Neuritis Treatment Trial, which has previously reported a relationship between optic neuritis and multiple sclerosis. [1][2][3][4] The Optic Neuritis Treatment Trial looked at the clinical findings, natural history, and treatment aspects, but unfortunately only included adults with optic neuritis.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of prospective clinical data in children to support its use, high-dose intravenous methylprednisolone is considered first-line treatment for pediatric optic neuritis by extension from the ONTT, as affected children often present with impairment of visual acuity severe enough to justify its use. Following IVCS, a prolonged oral corticosteroid taper over 2-6 weeks is common, as some experts believe there is an increased rate of relapse with early cessation of corticosteroids (27,29,30). One recent small retrospective study of 26 consecutive pediatric patients with optic neuritis treated for 3 days with intravenous methylprednisolone compared those treated with an additional two weeks of oral corticosteroids to those treated for more than two additional weeks.…”
Section: Corticosteroids In Pediatric Optic Neuritismentioning
confidence: 99%
“…4 Optic neuropathy and CN VIII disease often requires prolonged therapy, warranting a slower steroid taper or use of TNF-α antagonists like infliximab. 47 Mild symptomatic hydrocephalus will respond to corticosteroid treatment, but severe hydrocephalus will require ventricular drainage in addition to immunosuppressant therapy. Peripheral neuropathy and myopathy may occasionally respond to shorter courses, but often require prolonged therapy.…”
Section: Treatmentmentioning
confidence: 99%